Comunicação nas políticas sociais : a busca pela interlocução entre os serviços e as/os usuárias/os em âmbito municipal - Soares, Jéssica Degrandi (2023)
The present thesis deals with the debate on the communication between social policies and users in the search for the guarantee of rights. It aims to analyze how communication is established between the services provided by health, social assistance and education policies and users who seek access to their rights at the municipal level. The study departs from historical and dialectical materialism in Marx, characterized as an exploratory mixed type, as it articulates quantitative and qualitative data. The methodological path used was based on research techniques such as: literature review, bibliographical research, documental research and semi-structured interview. To analyze the data, content analysis in Bardin (2010) was used. The specific objectives were answered through the results listed in the methodological path, which are: Identifying the debates carried out in the production of knowledge of Social Work on the theme of communication between users and social policies; Identify users' rights of access to information, provided for in legislation related to health, social assistance and education policies; Analyze the communication strategies used by the municipality studied to inform users of social policies about their rights; Analyze factors that favor or hinder the processes of communication between the State and the users of social policies. Based on this construction, the thesis is defended that in the context of knowledge production, information and communication are recognized as a right and that Social Work is responsible for tensioning and highlighting this debate more and more. Within the scope of legislation, it is necessary that the documents that guide the services discuss information in a broader way, mainly guaranteeing the bias of the dialogue between services and the user population. From the strategies of the professional teams, the effort made to guarantee at some level the right to information and communication is evidenced, but they need support to articulate this right more effectively, as specialized communication professionals to think about targeted communication policies for the population. And from the factors that favor and hinder it, it is evident that communication does not follow a single path, and that it needs collective work between managers, workers and users to happen. It is identified that there is a long path in the scope of deepening public communication so that communicative processes are in fact evidenced, and that ethical communication is fostered, aligned with social rights and with a view to strengthening the interests of the working class. It is highlighted that there are many challenges, in the context of mass communication and breaking with market discourses, while it is clear that there is a portion of the population committed to emancipatory processes within the scope of the right to information and communication, whether in the production of knowledge, at the forefront of social policies and in the organization of users of social policies.